Qualidade de vida de famílias que têm filhos com deficiência intelectual moderada em São Carlos, SP, Brasil - Oliveira, Érica Bueno Camargo de (2019)
Aims: This study investigated the impact of moderate ID on family quality of life (FQoL) on a sample of families from the city of São Carlos, SP, Brazil. Methodology: It’s a descriptive and cross-sectional research, in which 50 families with children with moderate ID and linked to the Association of Parents and Friends of Exceptional (APAE) of São Carlos participated. The data was collected using forms applied face-to-face, with families’ sociodemographic information, personal information from the individuals with ID, the Barthel and the Lawton & Brody functionality indexes of individuals with ID, and the Beach Center Family Quality of Life Scale (BCFQoLS). For statistical analysis, parametric tests were used. The statistical significance of the differences was determined by t-test or ANOVA, depending on the numbers of variables analyzed. The Pearson correlation test was used to evaluate the degree of binary correlation between the FQoL and the other variables, and the linear regression method was used for multiple correlation analysis. The level of significance adopted was 5%. Results: The individuals with ID reached an average of 90 points (SD±13.36) in the Barthel index, indicating moderate dependence for activities of daily living; and 3.12 points (SD±1.66) in the Lawton & Brody index, indicating a severe dependency for instrumental activities of daily living. The mean score reached in BCFQoLS was 3,587 (SD±0.470); this value of total QVF was significantly higher than the scores obtained in the domains "emotional well-being" and "physical/material well-being", and significantly lower than the scores obtained in the "family interaction" domains, "parenting" and "disability-related support". Emotional well-being was the domain with the lowest score in relation to the other domains. The domains most strongly correlated with total FQoL were "family interaction", "parenting” and "emotional well-being", aspects intrinsically modulated by family dynamics and cohesion. The only variable that showed a significant binary correlation with the total FQoL was the Lawton & Brody index (r=0.326; p=0.021). The adjusted linear regression model, considering this index, explained 10.6% of the variability found in the total FQoL results (p=0.021) and showed that the increase of one unit in the value of the Lawton and Brody index represented an increase of 0.092 points in the total FQoL value. Final considerations: It was observed that the FQoL of families with children with ID in the city of São Carlos, SP, is below the results of most international studies. The domain with the lowest scores was "emotional well-being". It is recommended that actions be taken to strengthen the dialogue and family cohesion in order to strengthen relationships and care among members. It is also important to offer activities that stimulate tasks of basic and instrumental activities of daily living early on, in order to promote greater autonomy of the disabled individual. Finally, it will be important to develop actions to raise awareness and training of public opinion, in order to facilitate a change of attitude that allows improvement in the integration of people with ID in society, promoting the exercise of citizenship.